BANGKIT DARI KETERTINDASAN (Studi atas Pemikiran Kesetaraan Gender Fatayat NU) - Safri, Arif Nuh (Musawa Jurnal Studi Gender dan Islam, 2012)
Fatayat NU is one of the Islami cwomen's organizations in Indonesia. This organization has a goal, deletionall forms of violence, injustice and poverty in the community by developinga constructivediscourseof sociallife, democracy and gender justice. Therefore, throught his organizational sobuilds awareness of women's criticalto realizing gender equality and justice. Throughthis article, I will explain howFatayatNUtried tobuild an opinionand fighting forthe rights of womento beable to rise fromoppression